2018
DOI: 10.1021/acs.biochem.8b00028
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Regulation of Staphylococcus aureus Phosphofructokinase by Tetramer–Dimer Conversion

Abstract: Most reported bacterial phosphofructokinases (Pfks) are tetramers that exhibit activity allosterically regulated via conformational changes between the R and T states. We report that the Pfk from Staphylococcus aureus NCTC 8325 ( SaPfk) exists as both an active tetramer and an inactive dimer in solution. Multiple effectors, including pH, ADP, ATP, and adenylyl-imidodiphosphate (AMP-PNP), cause equilibrium shifts from the tetramer to dimer, whereas the substrate F6P stabilizes SaPfk tetrameric assembly. Crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…This study showed that SprC could impact PTS by regulating mtlA (SAOUHSC_02402) encoding one PTS enzyme. ATP-dependent 6-phosphofructokinase encoded by SAOUHSC_01807 ( pfkA ) is the key enzyme in the first committing step of glycolysis ( Tian et al, 2018 ). However, whether SprC has the function of regulating the expression of this enzyme remains to be confirmed, because in this study there were inconclusive results on the expression of pfkA ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that SprC could impact PTS by regulating mtlA (SAOUHSC_02402) encoding one PTS enzyme. ATP-dependent 6-phosphofructokinase encoded by SAOUHSC_01807 ( pfkA ) is the key enzyme in the first committing step of glycolysis ( Tian et al, 2018 ). However, whether SprC has the function of regulating the expression of this enzyme remains to be confirmed, because in this study there were inconclusive results on the expression of pfkA ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because few bacterial PFK-1 structures have been experimentally solved [41][42][43][44][45] , we instead compiled a diverse set of sequences from the Uniprot database as inputs for structural prediction using AlphaFold2 46 , and subsequently modeled PEP into the allosteric pocket of each model by structural alignment with the previously solved mutant Geobacillus stearothermophilus PFK-1-PEP (PDB: 4I4I) complex (Figure 5A) (all-atom RMSD of the binding pocket = 0.371 Å; global RMSD = 0.493 Å). 41 We optimized each ortholog's PFK-1 model to a stable, energetically favorable conformation without steric clashes in the pocket using the relax application in the Rosetta macromolecular modeling software.…”
Section: Case Study 3: Trends In Inhibitor Binding For An Evolutionar...mentioning
confidence: 99%
“…Several X-ray crystallographic structures deposited at the Protein Data Bank for three glycolytic enzymes phosphofructokinase (PFK), glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and pyruvate kinase (PK) were extracted for species of Homo sapiens (H. sapiens) (Kung et al, 2012;Kloos et al, 2015;White et al, 2015), Staphylococcus aureus (S. aureus) (Mukherjee et al, 2010;Axerio-Cilies et al, 2012;Tian et al, 2018) and three parasites, Trypanosoma cruzi for GADPH (T. cruzi) (Guido et al, 2009), Trypanosoma brucei (T. brucei) for PFK (McNae et al, 2009) and Leishmania mexicana (L. mexicana) for PK (Rigden et al, 1999) and the selected ones were listed in…”
Section: System Preparationmentioning
confidence: 99%
“…The proposed druggable site encircled in the left figures clearly indicate the active tetramer form displaying a lower degree of frequency shift compared to dimer form. Consequently, the number of druggable sites which satisfied the frequency (Kloos et al, 2015;Tian et al, 2018). ATP and F6P were illustrated with orange and yellow sticks.…”
Section: S Aureus Phosphofructokinase (Sapfk) Indicated An Alternative Allosteric Region In Addition To Well-known Allosteric and Catalytmentioning
confidence: 99%
See 1 more Smart Citation